Chicken authentication and discrimination via live weight, body size, carcass traits and breast muscle fat content clustering as affected by breed and sex varieties in Malaysia - Nematbakhsh, Sara; Selamat, Jinap; Idris, Lokman Hakim; Abdull Razis, Ahmad Faizal (Multidisciplinary Digital Publishing Institute, 2021)
Nowadays, the high demand for village chickens in Malaysia leads to the fraudulent substitution of indigenous chickens with other cheaper counterparts. Discriminating different chicken breeds based on their phenotypic characteristics is one strategy to avoid chicken adulteration. The main objective of this study was to authenticate and group dominant chicken breeds in Malaysia, including commercial chickens (Cobb, Hubbard, DeKalb) and cross-bred village chickens (Ayam Kampung, Akar Putra). The further discrimination of village chickens from underaged colored broilers (UCBs) (Hubbard, Sasso) was performed based on phenotype traits. The results showed that the breed had a significant effect (p < 0.05) on phenotypic characteristics, while the sex effect was not significant for some characteristics. In the first phase, the most remarkable discriminating factors were abdominal fat weight, breast muscle weight, chest circumference, shank length, and wingspan. However, in the second phase, notable variations in phenotypic characteristics between village chickens and UCBs were not detected. Principal component analysis (PCA) showed the successful separation of village chickens from high-performance breeds (broiler and colored broiler). Nevertheless, there was overlap among observations for Sasso and village chickens, which approved the possible similarities in their phenotypic characteristics. This study showed clear breed clustering, which leads to the chicken authentication based on their phenotypic characteristics.